New Horizons for a Data-Driven Economy A Roadmap for Usage and Exploitation of Big Data in Europe - Cavanillas, José María; Curry, Edward; Wahlster, Wolfgang (Springer Nature, 2016)
Information Storage and Retrieval; Innovation/Technology Management; Computer Applications; Computers and Society; Big data